2010
DOI: 10.1159/000321008
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Hydronephrosis Predicts Advanced Bladder Cancer but Is Not an Independent Factor for Cancer-Specific Survival after Radical Cystectomy

Abstract: Introduction: Hydronephrosis and BMI are analyzed together with established factors such as TNM stage and surgical margins in a multivariate modality to investigate their status as independent prognostic factors for bladder cancer-specific survival in patients undergoing radical cystectomy. Patients and Methods: We studied a prospective cohort of 328 patients who underwent radical cystectomy for bladder cancer at our institution. Statistical analyses were performed using the Kaplan-Meier method, Kendall-tau ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…All studies were published between 2004 and 2015, with the mean duration of follow-up varying from 20 to 148 months. Of the 36 studies, 14 were conducted in North America [4, 820], 8 in Europe [2128], 6 in Asia [7, 2933] and 8 at international multicenters [3441]. The meta-analysis was based on a total sample size of 38,384 patients, of which 4,354 patients were reported to have positive surgical margins.…”
Section: Resultsmentioning
confidence: 99%
“…All studies were published between 2004 and 2015, with the mean duration of follow-up varying from 20 to 148 months. Of the 36 studies, 14 were conducted in North America [4, 820], 8 in Europe [2128], 6 in Asia [7, 2933] and 8 at international multicenters [3441]. The meta-analysis was based on a total sample size of 38,384 patients, of which 4,354 patients were reported to have positive surgical margins.…”
Section: Resultsmentioning
confidence: 99%
“…Many patients with bladder cancer were found to have hydronephrosis due to ureteral orifice obstruction by tumor. Although pathologic stage is regarded as crucial prognostic characteristic after radical cystectomy, the prognostic role of hydronephrosis has been investigated with conflicting results . To the best our knowledge, the relationship between the presence of preoperative hydronephrosis and prognosis after RARC has not yet been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Although pathologic stage is regarded as crucial prognostic characteristic after radical cystectomy, the prognostic role of hydronephrosis has been investigated with conflicting results. [19][20][21][22] To the best our knowledge, the relationship between the presence of preoperative hydronephrosis and F I G U R E 1 Receiver operating characteristic (ROC) curves for overall survival prognosis after RARC has not yet been investigated. In our study, we found that preoperative hydronephrosis was significantly associated with 1-year mortality after RARC according to univariate cox regression.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, most studies identify patient comorbidity as an important risk factor for complications after radical prostatectomy. Importantly, obesity by itself does not seem to be an independent risk factor [29]. …”
Section: Discussionmentioning
confidence: 99%